Iron deficiency in heart failure with preserved ejection fraction: a systematic review and meta-analysis - Beale, Anna L (Open Heart, 2019)
OBJECTIVE: Iron deficiency (ID) has an established impact on outcomes in patients with heart failure with reduced ejection fraction; however, there is a lack of conclusive evidence in patients with heart failure with preserved ejection fraction (HFpEF). We sought to clarify the prevalence and impact of ID in patients with HFpEF. METHODS: A systematic search of Cohcrane, MEDLINE, EMBASE, Web of Science and CINAHL electronic databases was performed to identify relevant studies. Included studies defined HFpEF as heart failure with an ejection fraction ≥50%. We used a random-effects meta-analysis to determine the composite prevalence of ID in patients with HFpEF across the included studies. Other outcomes were assessed with qualitative analysis due to a paucity of studies with comparable outcome measures. RESULTS: The prevalence of ID in the included studies was 59% (95% CI 52% to 65%). ID was associated with lower VO(2) max in three of four studies reporting VO(2) max as an outcome measure, lower functional status as determined by dyspnoea class or 6 min walk test in two of three studies, and worse health-related quality of life in both studies reporting on this outcome. Conversely, ID had no impact on death or hospitalisation in three of the four studies investigating this. CONCLUSIONS: ID is highly prevalent in patients with HFpEF and is associated with worse exercise capacity and functional outcomes, but not hospitalisation or mortality. Our study establishes that ID may play an important a role in HFpEF.